ENT 600 : Blueprint : Convenient thermos (CT) / Muhammad Nizamul Hakim Norzaki ...[et al.] - Hakim Norzaki, Muhammad Nizamul; Awg Osman, Dygku Aniqnatasa; Arzman, Nuriman Aimi; Zainol, Nur Syuhada (2019)
Convenient Thermos (CT) is the product to be developed. Thermos are one of product that suitable and conducive for all generations. It is used to prevent heat loss and keep the warmness of the drink for a certain time. Therefore, the purpose of this project is to reheat users drink when drink temperature is below than 30°C which very convenient to employee and household.